Taxonomic notes and synonymy in Crotalaria montana (Fabaceae: Crotalarieae) - Lohit, Tushar Anilrao; Wagh, Vijay Vishnu (Phytotaxa, 2024)
The taxonomic identity of newly described Crotalaria lamelliformis is resolved here. Very recently C. lamelliformis has been synonymised under Crotalaria albida, but after examination of protologue and a large number of specimens of C. albida deposited in different herbaria, it is concluded that the newly described C. lamelliformis is erroneously identified and its correct identity is C. montana based on the distinct morphological as well as micro-morphological characters. For the easy identification of C. montana a detailed description, field photographs, illustration and comparison with C. albida is provided.